Evaluation of cardiorespiratory fitness and Its correlation with team performance, player position and physical characteristics in the soccer Premium League of Iran - Angoorani, H.; Basharkhah, A.; Mazaherinezhad, A.; Nazari, A. (Asian Journal of Sports Medicine, 2021)
Background: This study is one of the first to specifically analyze cardiorespiratory fitness and its association with age, weight, height, body fat percentage (BFP), body mass index (BMI), team performance, and player position for a large number of soccer players in an Asian top league. Methods: 213 players (age = 25 ± 5 years, height = 181.2 ± 6.8 cm, weight = 76.1 ± 8.1 kg, BFP = 11.3 ± 3.1) affiliated with 16 soccer clubs from Iran`s Premier League (i.e., the highest level of club football in Iran), were tested for maximal aerobic power (VO2 max), first and second ventilatory thresholds (VT1 and VT2), and ventilatory efficiency at rest (VO2 rest). The nonparametric Spearman's correlation test was performed to check for correlations, and the resulting rank correlation coefficients (rs) and probability value (P) are presented. Results: In terms of mean ± standard deviation, the 213 male players participating in this study have VO2max = 55.3 ± 5.4 mL.kg-1.min-1, VT1 = 57.3 ± 4.2 (% max), VT2 = 92.6 ± 3.4 (% max) and VO2rest = 7.1 ± 1.4 mL.kg-1.min-1. No correlation between VO2max and team performance or BFP was observed. The correlations between VO2max and age (rs= -0.23, P = 10-3), height (rs = -0.34, P ? 0), weight (rs = -0.42, P ? 0) and BMI (rs = -0.30, P = 10-5) were considered statistically significant. The difference between VO2max of players in different positions was also statistically significant. Goalkeepers possessed the lowest VO2max, with a mean value of 49.8 mL.kg-1.min-1. Defenders had the lowest mean VO2max value players (equal to 54.7 mL.kg-1.min-1) amongst outfield players, and midfielders had the highest mean VO2max (= 56.9 mL.kg-1.min-1). The other indices of cardiorespiratory fitness (VT1, VT2 and VO2rest) had no statistically significant correlation with the physical characteristics of the soccer players, team performance and player position. Conclusions: The study demonstrates that VT1, VT2, and VO2rest are not distinguishing factors amongst different categories of age, weight, height, team performance, and player position, but VO2max varies with age, weight, height, and BMI. The study also shows that there is a high correlation between the physical demands of player positions during a game and the aerobic capacity of players in those positions, and this must be taken into account in soccer training.